Comparative study on sustained release of metoclopramide salt from poly(D,L-lactide) and poly(D,L-lactide-co-glycolide) in-situ depots: formulation effects on drug release - Man, Shu Mei. (2009)
In this research project, in situ depot drug delivery system was studied. This system is made up of biodegradable polymers, that are poly(d,l-lactide) (PDLLA) and poly(d,l-lactide-co-glycolide) (PLGA), dissolved in n-methyl-2-pyrrolidone (NMP). Metoclopramide monohydrochloride (metosalt) was used as a low molecular weight model drug. A semi-solid depot will be formed upon injection of such system into body fluids and delivers drug constantly in a controlled manner. This study consists of three main parts: (1) The solvent release characteristics upon depot formation, (2) the drug release characteristics of low molecular weight drug from the depots and (3) the degradation characteristics upon depot formation. The solvent and drug release were characterized using UV-Vis spectrophotometer and the degradation process was characterized using gel permeation chromatography. All three processes were found to be dependent on the formulation of the drug-loaded polymer solution. PDLLA depots were formed through fast solvent exchange process that led to burst initial release of drug and subsequent diffusion will proceed at a decreasing rate without degradation. PLGA depots were formed through slower solvent exchange process that led to slower and steady release of drug initially, followed by degradation that led to burst release of drug at the later stage. It was also found that functionalization increased the rate of hydrolysis and drug release. Degree of drug loading will affect diffusion release which depends on the solubility of drug in the continuous phase and higher drug loading can increase degradation release due to osmotic effect.